2014
DOI: 10.7287/peerj.preprints.693v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV and AIDS related knowledge and attitudes towards learners infected with HIV: Survey among high school learners in Gauteng and North West provinces in South Africa

Abstract: The success of the proposed HIV testing and counselling (HTC) initiative among learners at high school in South Africa depends on their acceptability of the service, which may be influenced by their HIV/AIDSknowledge, perceptions, and attitudes. The study assessed high school learners’ HIV knowledge and attitudes towards learners infected with HIV. The survey was part of formative evaluation with grade 10-12 learners in order to assess the acceptability of HTC at schools. The study consisted of 17 high schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
3
0
0
Order By: Relevance
“…This can be attributed to the mandatory inclusion of HIV in school curriculum and an active particpication of teachers in imparting such valuable knowledge. Similar findings were reported by Sphiwe et al 5 for the knowledge of HIV/ AIDS attributed to the life orientation curriculum in Africa. In contrast studies by Pankaj Kumar et al 6 and Yazdi et al 7 independently revealed that television was the most common source of information while teachers contributed for a smaller proportion in the first study, teachers (66%) were pointed out as the next best source of information in Iran.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This can be attributed to the mandatory inclusion of HIV in school curriculum and an active particpication of teachers in imparting such valuable knowledge. Similar findings were reported by Sphiwe et al 5 for the knowledge of HIV/ AIDS attributed to the life orientation curriculum in Africa. In contrast studies by Pankaj Kumar et al 6 and Yazdi et al 7 independently revealed that television was the most common source of information while teachers contributed for a smaller proportion in the first study, teachers (66%) were pointed out as the next best source of information in Iran.…”
Section: Discussionsupporting
confidence: 90%
“…The difference may be due to the different periods of study. A low proportion of misconceptions about transmission of HIV through sharing toilets, sharing plates, etc was observed, however, more than a half of them had misconceived that HIV is transmitted by mosquitoes (53.4%) which was similar to the findings of Prathiba Gupta et al 10 Knowledge on prevention and control of HIV revealed that less than 60% responded correctly with regard to absence of an available vaccine against HIV, alcohol and risky behaviours increases risk of HIV, presence of a cure for HIV and about implementation of laws for discrimination against people living with HIV in this study, which were similar to the findings of Pankaj Kumar et al 5 and Jaiswal et al 11 which shows that correct knowledge regarding availability of vaccine for prevention of pretest were 28 (27.45%) and 46.2% respectively. The misconceptions are caused due to a gap in knowledge.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, in this study, a strong positive significant association was found between educational level and acceptance attitude towards PLHA in all the three countries. Other similar studies were reported from different regions of the world [28, 31,38,45,46].…”
Section: Acceptance Attitudes Of Male Youthsupporting
confidence: 74%